COMPARATIVE STUDY OF THE DOCTRINE OF REPUDIATION OF CONTRACT IN THE CONTRACT FOR THE INTERNATIONAL SALE OF GOODS (CISG) AND THE TERMS OF CANCELLATION IN THE CIVIL CODE - Setiasih, Herma; Haryadi, Wahyu Tris; Rosmaya, Ina; Ardhana, Annisa Sofia (jfpublisher, 2024)
In International Civil Law, several types of breach can be found, one of which is anticipatory breach. The term anticipatory breach has its roots in the concept of repudiation, which covers a wider range of refusals. Repudiation includes not only anticipatory breach, but also every form of refusal to fulfill contractual obligations, both before and after the contract period begins. Anticipatory breach refers to actions that indicate one party's intention not to fulfill its contractual obligations to the other party. This research aims to analyze how the Contract for the International Sale of Goods or CISG and the Civil Code regulate the return of rights for breach committed by one of the parties. The method applied is normative juridical research with statute and comparative approach. The findings of this research indicated that validity of an agreement under Article 1320 of the Civil Code requires an agreement, capacity, a specific object, and a lawful cause. If these subjective and objective conditions are unmet, or if there is a breach causing harm, the agreement may be canceled, but only through a court decision as per Article 1266. Repudiation, the refusal to fulfill an agreement, has two models: the mirror image model and the differentiated model, which assess potential future losses. In international civil law, anticipatory breach, a concept linked to repudiation, is covered in Articles 71-73 of the CISG.